2017
DOI: 10.6063/motricidade.6138
|View full text |Cite
|
Sign up to set email alerts
|

Level of resilience in non-practicing and practicing physical exercise in elderly

Abstract: RESUMOO objetivo deste estudo foi analisar o nível de resiliência de idosas praticantes (GP) e não praticantes de exercício físico (GNP), conforme os aspectos sociodemográficos, condições de saúde e eventos estressantes. Participaram 164 idosas, sendo 85 do GP e 79 do GNP. Utilizou-se uma ficha diagnóstica para coletar dados sociodemográficos, as condições de saúde, o Inventário de Eventos Estressantes e a Escala de Resiliência. Empregou-se a estatística descritiva e inferencial. Não houve diferença significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
1
2
0
2
Order By: Relevance
“…In the current investigation, the greater the number of morbidities, the lower the resilience score. It is known that stressful situations in the elderly's life, such as living with comorbidities, make this population more susceptible to negative feelings, which can affect their adaptation pattern, consequently, their resilience (35) . A study carried out among individuals with CNCDs found that the longer duration of morbidity negatively influenced the resilience score (p=0.014) (36) .…”
Section: Discussionmentioning
confidence: 99%
“…In the current investigation, the greater the number of morbidities, the lower the resilience score. It is known that stressful situations in the elderly's life, such as living with comorbidities, make this population more susceptible to negative feelings, which can affect their adaptation pattern, consequently, their resilience (35) . A study carried out among individuals with CNCDs found that the longer duration of morbidity negatively influenced the resilience score (p=0.014) (36) .…”
Section: Discussionmentioning
confidence: 99%
“…Despite this body of evidence, the role of physical activity in the association between resilience and mental health in older adults remains largely unexplored. In the present study, the individuals in the Sufficiently physically active group exhibited stronger associations between resilience and mental health as compared to the Insufficiently physically active group, corroborating findings of our previous baseline analysis and also of other cross-sectional studies Mazo et al, 2016). Nevertheless, our study made advancement compared to previous studies, yielding longitudinal data and furthering understanding on the components of resilience used in this relationship.…”
Section: Discussionsupporting
confidence: 91%
“…Stressful Events Inventory consists of 31 items that indicate negative events, such as health problems or marital relationships and parental death, being used to measure the impact of these stressful events on the interviewee's life (17) .…”
Section: Study Protocolmentioning
confidence: 99%